Isoproterenol-Dependent Activation of TRPM7 Protects Against Neurotoxin-Induced Loss of Neuroblastoma Cells - Sun, Yuyang; Kamat, Amrita; Singh, Brij B. (Frontiers in Physiology, 2020)
Neuronal function and their survival depend on the activation of ion channels. Loss of ion channel function is known to induce neurodegenerative diseases such as Parkinson’s that exhibit loss of dopaminergic neurons; however, mechanisms that could limit neuronal loss are not yet fully identified. Our data suggest that neurotoxin-mediated loss of neuroblastoma SH-SY5Y cells is inhibited by the addition of β-adrenergic receptor (β-AR) agonist isoproterenol. The addition of isoproterenol to SHSY-5Y cells showed increased Mg2+ influx and cell survival in the presence of neurotoxin especially at higher concentration of isoproterenol. Importantly, isoproterenol potentiated transient receptor potential melastatin-7 (TRPM7) channel activation that leads to an increase in intracellular Mg2+ levels. The addition of 2APB, which is a known TRPM7 channel blocker, significantly decreased the TRPM7 function and inhibited isoproterenol-mediated protection against neurotoxins. Moreover, neurotoxins inhibited TRPM7 expression and function, but the restoration of TRPM7 expression increased neuroblastoma cell survival. In contrast, TRPM7 silencing increased cell loss, decreased Mg2+ homeostasis, and inhibited mitochondrial function. Moreover, isoproterenol treatment prevented neurotoxin-mediated loss of TRPM7 expression and inhibited Bax expression that induces cell survival. These effects were dependent on the neurotoxin-induced increase in oxidative stress, which inhibits TRPM7 expression and function. Together, our results suggest a positive role for β-AR in activating TRPM7 channels that regulate Mg2+ homeostasis and are essential for the survival of SH-SY5Y cells from neurotoxin.